Motivação para o trabalho: rotina e fragmentação das tarefas - Santos, Jesse Ambrosio dos (1988)
The present dissertation deals with the problems concerning the motivation to work, wich comes excessive fragmentation of the tasks. from the We do not intend to suggest solutions for the problem. What we have done is a criticaI analysis over it joining our effort to other allies more capable and more valuable in order to warn those who are engaged in the very subject with power of decision,rousing them to look for a solution, one resolution for the problem; whithout strangling the economy nor atrophying technological advancement. We initiate the text with a discussion over the functions of the work, its concepts, followed by a critical analysis over the division of the work and fragmentation of the tasks. In sequence, we have done one brief exposition over motivation, its conceptual and his torical evolution, continued by an analysis over theoretical assumptions of psychology's different currents. There is afterwards a discussion over the problems of the motivation for the work, where we emphasize the contributions of Maslow, Herzberg and McClelland. We finish it with a discussion of the problems the dissertation has dealed with;when we show our personal critics and conclusions over the subject.